PREPARATION OF PATIENTS FOR LABORATORY AND INSTRUMENTAL EXAMINATIONS (Modern education and development, 2025)
The preparation of patients for laboratory and instrumental examinations is a critical step in the diagnostic process. Proper preparation ensures the accuracy of test results, which is essential for making precise diagnoses. This article outlines the key guidelines and methods for preparing patients for various laboratory and instrumental examinations.